Pengaruh Gaya Kepemimpinan Transaksional Melalui Motivasi Terhadap Kinerja Karyawanan Pada Bank Pembangunan Daerah Kalimantan Selatan (Kantor Cabang Utama Banjarmasin) - Nanang Setiaji; Rasyidi Rasyidi; Siti Rusidah (Universitas Lambung Mangkurat, 2016)
The purpose of this research is test the influence of transactional leadership style (X) and the motivation (Z) againts employee performance (Y) in Bank Pembangunan Daerah Kalimantan Selatan (Kantor Cabang Utama Banjarmasin).Samples taken as many as 78 people which is the overall number of employees (excluding the branch leader and section leader). Collecting data using the questionnaire while data analysis using the PLS (Partial Least Square) by using the smartPLS.The test results prove the transactional leadership style have a significant effect on employee motivation with the effect of 38.08%, motivation significantly influence performance of employees with the effect of 2.40%, transactional leadership style significantly influence employee performance with the effect of 59, 96%.Key words: transactional leadership style, motivation and employee performance